2021
DOI: 10.26444/jpccr/132398
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of an educational training programme on blood glucose monitoring among nurses in the management of hypoglycaemia and hyperglycemia

Abstract: Ojemola. Outcome of an educational training programme on blood glucose monitoring among nurses in the management of hypoglycaemia and hyperglycemia. J Pre-Clin Clin Res.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…A tertiary hospital study in Nigeria among Nurses on the management of diabetes mellitus showed that educational intervention training could improve knowledge of the management of diabetes mellitus [22]. Protocols and guidelines were recommended to be placed in strategic positions in the hospitals to assist the nurses in the management of the patients.…”
Section: Discussionmentioning
confidence: 99%
“…A tertiary hospital study in Nigeria among Nurses on the management of diabetes mellitus showed that educational intervention training could improve knowledge of the management of diabetes mellitus [22]. Protocols and guidelines were recommended to be placed in strategic positions in the hospitals to assist the nurses in the management of the patients.…”
Section: Discussionmentioning
confidence: 99%
“…It must be taken into consideration that the use of educational programmes are an important part of DM control [14]. Analysis of the application data was also useful for demonstrating the prevalence of the involvement of patients in general, considering the population under analysis (patients already diagnosed with type 2 diabetes mellitus and under medication control), showing the relationship between personal antecedents with diabetes -75% of diabetic patients also had associated hypertension.…”
Section: Ulcerationsmentioning
confidence: 99%